Oral oncolytic and antiretroviral therapy administration: dose adjustments, drug interactions, and other considerations for clinical use - Melissa E Badowski; Bradley Burton; Kristy M Shaeer; John Dicristofano (BioExcel Publishing Ltd, 2019)
The rise in non-AIDS defining cancers (NADCs) is emerging as a leading cause of death for HIV and cancer patients. To address this, current literature and guidelines suggest the continuation of antiretroviral therapy (ART) with oral oncolytic agents to prevent adverse complications associated with HIV disease progression. However, such an approach has the potential for drug-drug interactions and adverse events for patients on such therapy. Further, recommendations on how to adjust these medications, when used concomitantly, are limited. As such, our purpose is to evaluate existing literature through such means as drug databases (e.g. Micromedex, Lexi-Comp, etc.) and package inserts along with PubMed/Medline, Embase, and Google Scholar databases to develop a reference tool for providers to utilize when there is a decision to treat a patient with ART and oral oncolytic agents concurrently. Our findings suggest that there are many drug interactions that should be taken into consideration with dual therapy. Metabolism is a key determinant of dose adjustment, and many oncolytic agents and ART agents must have their dose adjusted as such. Most notably, several tyrosine kinase inhibitors require dose increases when used with non-nucleoside reverse transcriptase inhibitors (NNRTIs) but must be decreased when used concomitantly with protease inhibitors (PIs) and cobicistat. Further findings suggest that certain agents should not be used together, which include, but are not limited to, such combinations as bosutinib with NNRTIs, cobicistat, or PIs; idelalisib with maraviroc or PIs; neratinib with NNRTIs, cobicistat, or PIs; and venetoclax with NNRTIs. Overall, the most prominent oncolytic drug interactions were discovered when such agents were used concomitantly with PIs, cobicistat-boosted elvitegravir, or NNRTIs. Future studies are necessary to further evaluate the use of these agents together in disease therapy to generate absolute evidence of such findings. However, from the studies evaluated, much evidence exists to suggest that concomitant therapy is not without drug interactions. As such, clinical decisions regarding concomitant therapy should be evaluated in which the risk and benefit of dual therapy are assessed. Dose adjustments must be made accordingly and in consultation with both HIV and oncology clinicians and pharmacists to reduce the risk for adverse outcomes and disease progression for those with cancer and HIV/AIDS.